The effect of ant-plant (Hydnophytum formicarum) ethanol extract on collagen fibers for wound healing after tooth extraction in the guinea pig (Cavia cobaya) - Velanita, Siti; Ismardianita, Efa; Pascawinata, Andries (Universitas Padjadjaran, 2019)
Introduction: Tooth extraction causes tissue damage around the socket. Wound healing is essential for repairing damaged tissues. One of the medicinal plants often used is ant-plant (Hydnophytum formicarum), which contains flavonoids, triterpenoids, saponins and tannins. This research was aimed to determine the effect of ant-plant ethanol extract on the density of collagen fibers for wound healing after tooth extraction in the guinea pig (Cavia cobaya). Methods: The type of research was true experimental with a post-test only control group design. The study used 48 male guinea pig divided into 4 groups. Experimental groups received lower left incisor extraction, the control group was orally administered with 0.5% CMC, and the treatment group was administered with ant-plant extract dissolved with 0.5% CMC with dose of 4.65 mg, 6.2 mg, and 9.3 mg respectively; each guinea pig was given 3 cc of the extract 3 times a day until the termination day. On day 3, 7, 14, and 21 respectively, the guinea pigs were terminated and to make the histological preparations. The difference in collagen fibers density of the two observation groups was tested with one-way ANOVA, and the LSD test to analyse the significance between groups. Results: Application of ant-nest ethanol extract showed significant effects on the density of collagen fibers in the wound healing process after tooth extraction. Results of the one-way ANOVA test showed significant value on all treatment groups (p < 0.05). There were also found significant differences between the control group and the treatment group (p < 0.05). Conclusion: Ant-plant (Hydnophytum formicarum) ethanol extract increase the collagen fibers density on the wound healing after tooth extraction with the effective dose of 4.65 mg.Keywords: Ant-plant, Hydnophytum formicarum, wound healing, collagen, guinea pig, Cavia cobaya.